A leakproof load-bearing non-woven fabric handbag and its manufacturing process

Through the multi-layer composite structure design and PLA vacuum adsorption penetration process, combined with secondary heating and differentiated cooling technology, the shortcomings of non-woven handbags in load-bearing, durability and functional integration are solved, and efficient and stable multi-function integration and mechanical performance improvement are achieved.

CN119348231BActive Publication Date: 2025-03-21SICHUAN KAIPU ECO-FRIENDLY PACKING PROD CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411918303.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-25
Publication Date
2025-03-21
Estimated Expiration
2044-12-25

AI Technical Summary

Technical Problem

The existing non-woven handbags have shortcomings in load-bearing, durability and functional integration, especially the single-layer structure has limited load-bearing capacity, and the multi-layer composite structure has the problem of insufficient bonding strength between layers. Needle-punching reinforcement will reduce flexibility, and surface treatment is difficult to achieve effective combination of multiple functions, and the functional durability is poor.

Method used

The multi-layer composite structure design is adopted, combining high-porosity PET needle-punched non-woven fabric and PLA vacuum adsorption penetration process, and through secondary heating and differentiated cooling processes, a structure that takes into account both local high stiffness and overall flexibility is formed. At the same time, an online inspection and quality control system is introduced to ensure the stability of product performance and batch consistency.

Benefits of technology

It significantly improves the load-bearing capacity and durability of the non-woven handbag, realizes the effective integration of multiple functions such as antibacterial, flame retardant, and waterproof, ensures the mechanical properties and anti-seepage characteristics of the product, maintains stable quality during long-term use and complex environments, and improves production efficiency and material utilization.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119348231B_ABST
    Figure CN119348231B_ABST
Patent Text Reader

Abstract

The present invention proposes a leakproof load-bearing non-woven fabric handbag and its manufacturing process, which relates to the technical field of non-woven fabric handbag manufacturing. A multi-layer composite structure design is constructed, and a layered non-woven fabric handbag manufacturing technology based on outer layer protection, middle layer function, and inner layer load-bearing is proposed; and on this basis, high-porosity PET needle-punched non-woven fabric and superheated melt PLA material vacuum adsorption penetration and differential cooling and other process steps are introduced. By strictly controlling the needle-punching density, PLA melting temperature, vacuum degree, secondary heating and bending / non-bending cooling rate, PLA can fully penetrate into the PET fiber pores and directionally enhance the local stiffness, which significantly improves the comprehensive performance of the handbag.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of non-woven fabric handbag manufacturing, in particular to a leak-proof load-bearing non-woven fabric handbag and a manufacturing process. Background Art

[0002] With the improvement of environmental awareness, non-woven bags are increasingly used in retail, logistics, medical and other fields. At present, the market demand for non-woven bags is showing a diversified trend, requiring them not only to have basic load-bearing functions, but also to meet multiple requirements such as durability, functionality and environmental protection. The manufacturing process of non-woven bags has gone through a development process from simple hot pressing to composite functional finishing, and has accumulated rich technical experience in material selection, structural design and process optimization.

[0003] The existing technologies mainly include the following categories: First, the traditional process of using a single layer of PP or PET non-woven fabric through hot pressing molding, which has the characteristics of simple process and low cost; second, the modification process of achieving waterproof, antibacterial and other functions through surface treatment methods such as coating and impregnation, which can give the product specific functional characteristics; third, the reinforcement process of multi-layer composite or needle punching reinforcement, trying to improve the load-bearing capacity and durability of the product; fourth, the emerging process of using new functional materials (such as nanomaterials, phase change materials, etc.) for modification to achieve special functional requirements. These technologies have been applied to varying degrees in production practice and have formed a relatively mature process system. However, there are still many problems that need to be solved in the existing technology.

[0004] The main problems of the existing technology include: the load-bearing capacity of the single-layer structure is limited, and the multi-layer composite structure has the problem of insufficient interlayer bonding strength and easy delamination; although the use of needle punching reinforcement can improve the strength, it will reduce the flexibility and service life of the product; in addition, the existing surface treatment method is difficult to achieve the effective combination of multiple functions, and the addition of functional materials often affects the mechanical properties of the product, and the functional durability is poor. The traditional hot pressing process has an uneven temperature field distribution, resulting in unstable product performance; the coating process has problems such as low material utilization and environmental pollution; there is a lack of effective online detection methods, product performance fluctuates greatly, and batch consistency is poor.

[0005] The technical problems to be solved by the present invention mainly include: through innovative multi-layer composite structure design and new manufacturing process, significantly improving the load-bearing capacity and durability of non-woven handbags, especially solving the problem of fatigue damage caused by repeated bending and use; how to achieve effective integration of multiple functions such as antibacterial, flame retardant, and waterproof through process innovation, while ensuring that the mechanical properties of the product are not affected; optimizing the production process, improving material utilization and efficiency, and realizing overall improvement of product performance and large-scale production; how to establish a complete online detection and quality control system to ensure the stability of product performance and batch consistency. Summary of the invention

[0006] In order to solve or partially solve the problems mentioned in the background technology, the present invention proposes a leakproof load-bearing non-woven fabric handbag and a manufacturing process, which innovatively introduces high-porosity PET needle-punched non-woven fabric and PLA vacuum adsorption penetration, secondary heating and differentiated cooling processes on the basis of multi-layer design. By allowing the PLA melt to fully penetrate into the PET fiber gaps and quickly solidify under a vacuum environment, and then rapidly cooling the bending parts and slowly cooling the non-bending parts after secondary heating, a structure with both local high stiffness and overall flexibility is obtained, thereby achieving a breakthrough in load-bearing capacity and bending fatigue life. Specifically, the process includes the following steps:

[0007] Step 1. Process and assemble three layers of functional materials, including an outer protective layer, a middle functional layer and an inner load-bearing layer.

[0008] First, the outer layer of PET or PP non-woven fabric is functionally treated by adding a hydrophobic agent with a concentration of 0.5-1.0% and a UV absorber with a concentration of 0.2-0.3%. The treated material is then dried at 120°C for 10-15 minutes to ensure that the functional additives are fully fixed on the fiber surface. Then, the middle functional layer is prepared, and the fiber with specific functions such as antibacterial, flame retardant, and odor absorption is compounded with a PTFE or PU microporous membrane with a thickness of 20-30μm. The membrane layer is firmly fixed on the fiber net with a density of 15-30g / m² by light pressure or low-temperature point bonding to form a middle layer structure with multiple functions. Finally, the inner layer of high-porosity PET needle-punched non-woven fabric is prepared. By precisely controlling the needle-punching density in the range of 800-1200 needles / cm² (preferably 1000 needles / cm²), it has a porosity of 30-40% (corresponding to an optimal porosity of about 34%), providing a good basic structure for subsequent PLA penetration.

[0009] Step 2: Use vacuum-assisted technology to infiltrate the molten PLA material into the multilayer structure to form a composite system.

[0010] First, PLA needs to be melted, PLA particles are heated to 200-220°C, and the melt viscosity is strictly controlled to be kept within the range of 2000-3000mPa·s, the stirring speed is maintained at 50-100rpm, and an online viscometer is used to test every 5 minutes to ensure that the viscosity fluctuation does not exceed 5%, so as to ensure that the melt has good fluidity and permeability. Then the prepared outer layer, middle layer and inner layer are stacked in sequence to form a sandwich structure, which is placed in a vacuum chamber, and the vacuum degree is pumped to -0.08~-0.1MPa by a vacuum pump. It is maintained for 3-5 minutes under this vacuum environment and temperature conditions, so that the PLA melt can fully penetrate into the pores of the inner layer of PET non-woven fabric. After the penetration is completed, cold air at 5-10°C is immediately introduced for rapid cooling for 5-10 seconds to achieve initial solidification of PLA in the pores of the PET fibers.

[0011] Step 3: Use temperature control technology to achieve differentiated distribution of mechanical properties in different areas of the product.

[0012] The composite material that has completed the initial curing is placed in a heating furnace equipped with an infrared thermometer, and the temperature is raised to 90-110°C and maintained for 3-5 minutes. During this process, the temperature gradient needs to be strictly monitored and adjusted to ensure that the temperature difference between the inside and outside of the material does not exceed 5°C, so that PLA can be uniformly transformed into a thermoplastic state. Then a differential cooling treatment is carried out. For the predetermined bending area, the temperature is quickly reduced from 95°C to below 30°C within 3 seconds by cold air spraying. This rapid cooling can improve the crystallinity and rigidity of the area; while for the non-bending area, it is placed in an incubator and the temperature is slowly reduced from 95°C to room temperature within about 10 minutes at a constant cooling rate of about 10°C / min. This differential cooling method can ensure that the bending area has sufficient rigidity while giving the non-bending area the required softness.

[0013] Step 4: Use multiple methods such as physical, functional and structural testing to ensure that product quality meets standards.

[0014] First, the physical properties of the product need to be fully tested, using the T-peel method to determine the interlayer bonding strength, testing the filling rate of PLA (required to reach more than 30%), and using the gas permeation method to determine the change in porosity. The second is the testing of functional performance, including testing the antibacterial rate (required to exceed 99%), using standard methods to test flame retardant properties (need to reach UL94V-0 level), and testing moisture permeability (required to be less than 1800g / m²·24h). Finally, structural defects are detected through precision instruments, using ultrasonic C-scanning with a resolution of 0.1 mm and X-ray imaging technology with an accuracy of 0.05 mm, to perform non-destructive testing on the inside of the product, timely discover possible defects such as delamination, cracks, and unfilled areas, and ensure that product quality meets requirements. The data of the entire testing process needs to be recorded in detail, and the process parameters are adjusted and optimized in a timely manner accordingly.

[0015] In addition, the present invention also provides a leak-proof and load-bearing non-woven fabric handbag, which is manufactured using the above process and achieves good load-bearing capacity, folding resistance, liquid leakage prevention and multiple functional integration through innovative combinations in structural design and material selection.

[0016] A leakproof load-bearing non-woven fabric handbag, comprising a multi-layer composite structure consisting of an outer layer, an intermediate functional layer and an inner load-bearing layer, wherein:

[0017] The outer layer is a hydrophobic and UV-resistant non-woven fabric layer, which is used to provide basic protection, UV resistance and weather resistance;

[0018] The middle functional layer is composed of a functional fiber layer and a microporous membrane layer. This layer has specific functions such as water blocking, antibacterial, flame retardant and odor absorption. It can effectively prevent liquid leakage, inhibit microbial growth and provide additional use functions.

[0019] The inner layer is a high-porosity PET needle-punched non-woven fabric, which is reinforced by hot-melt PLA material penetration to form the main load-bearing skeleton. Its pore structure solidifies after PLA melt penetration.

[0020] Furthermore, the outer layer non-woven fabric can use PET or PP as the base material, and add 0.5-1.0% of a hydrophobic agent and 0.2-0.3% of a UV absorber, and dry and shape it at 120°C, so that the fiber surface has continuous waterproof and UV resistance.

[0021] Furthermore, the middle functional layer can be made of antibacterial, flame retardant and deodorizing fibers and a PTFE or PU microporous membrane with a thickness of about 20-30μm. The microporous membrane is fixed on a lightweight fiber mesh (15-30g / m²) by low-temperature point bonding, so that this layer not only has a certain air permeability and waterproof and moisture permeability balance, but also can effectively inhibit fungi, reduce odor and improve the overall flame retardant level (reaching UL94V-0).

[0022] Furthermore, the inner layer uses a PET needle-punched nonwoven fabric with a high porosity (about 30-40%), forming a uniform porous structure under the condition of a needle-punching density of about 800-1200 needles / cm². When the PLA molten material penetrates the layer in a vacuum environment of -0.08~-0.1MPa, the PLA melt evenly fills the fiber pores and quickly cools and solidifies, thereby forming a reinforcement layer in which the PET fiber and the PLA continuous phase are cross-linked on the microstructure. This reinforcement layer has both high strength and moderate toughness, so that the handbag is not easy to break or deform when subjected to heavy loads and repeated bending.

[0023] Furthermore, in order to achieve regional differentiated performance, specific areas can be subjected to secondary heating (90-110°C) and differentiated cooling after PLA infiltration and curing:

[0024] Rapid cooling of the bend vulnerable area (from 95°C to below 30°C within seconds) to improve the crystallinity and stiffness of PLA and enhance the fatigue resistance of this area;

[0025] The non-bending area is cooled slowly (cooled to room temperature at a rate of about 10°C / min) to keep this area relatively soft, ensuring that the entire bag can be folded and stored when not in use without affecting the durability and flexibility of other parts.

[0026] The present invention realizes the integrated improvement of multiple functions of the non-woven fabric handbag in terms of load-bearing, durability, leak-proof, antibacterial, UV-proof, flame-retardant and deodorization through multi-layer composite structure design, PLA melt penetration enhancement and differentiated cooling control. Compared with traditional products, the handbag of the present invention can still maintain excellent mechanical properties and anti-seepage characteristics when fully loaded with heavy objects, and maintain stable quality under long-term use and complex environments. In addition, through online detection and precise control of process parameters, the consistency between batches and the repeatability of production are guaranteed, so that it has significant advantages in performance, function and environmental protection characteristics, which is conducive to large-scale promotion and application. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 This is a diagram showing the effect of PLA permeability on the mechanical properties of composite materials.

[0028] Figure 2 This is a diagram showing the regulatory effect of secondary heating temperature on the regional stiffness of the material. DETAILED DESCRIPTION

[0029] The present invention is further described in detail below through specific implementation modes.

[0030] The multi-layer composite structure of the handbag consists of three layers: outer, middle and inner. The material selection and performance requirements of each layer are as follows:

[0031] Outer layer: PET or PP non-woven fabric is used, treated with a hydrophobic agent (concentration 0.5-1.0%) and a UV absorber (concentration 0.2-0.3%), and dried at 120°C for 10-15 minutes. The outer layer plays a major protective role and needs to have excellent UV resistance, abrasion resistance and hydrophobic properties.

[0032] Middle layer: It is composed of functional fiber (antibacterial, flame retardant, odor absorption) and microporous membrane (PTFE or PU, thickness 20-30μm). The membrane layer is fixed on the fiber mesh (density 15-30g / m2) by light pressing or low-temperature point bonding. The middle layer gives the handbag specific functional properties, such as antibacterial rate ≥99%, flame retardant performance meeting UL 94V-0 level, and odor removal rate ≥90%.

[0033] Inner layer: High-porosity PET needle-punched non-woven fabric (needle density 800-1200 needles / cm2, porosity 30-40%) is used as the main substrate for PLA penetration. The inner layer is reinforced with PLA to form the main load-bearing skeleton of the bag, which is crucial to improving tensile strength and durability.

[0034] Through comparative tests, it can be seen that compared with traditional single-layer non-woven fabrics, the above-mentioned sandwich-type multi-layer structure has significant improvements in mechanical properties (tensile and tear strength), service life (wear resistance and bending resistance) and functionality (antibacterial and flame retardant effects).

[0035] On the basis of the three-layer structure, the present invention further innovatively introduces the PLA vacuum adsorption and penetration process to significantly improve the mechanical properties of the inner layer PET non-woven fabric. The process flow is as follows:

[0036] (1) Melting PLA pellets at 200-220°C and controlling the melt viscosity at 2000-3000 mPa·s;

[0037] (2) Place the PET / film / PET sandwich structure in a vacuum chamber (-0.08 to -0.1 MPa) and keep it at the above temperature for 3 to 5 minutes to allow PLA to fully penetrate;

[0038] (3) Allow cold air (5-10°C) to cool rapidly for 5-10 seconds to solidify PLA in the pores of PET fibers;

[0039] (4) Take out the composite material and reheat it at 90-110°C for 3-5 minutes to convert the PLA into a thermoplastic state;

[0040] (5) Use a differentiated cooling method: Rapid cooling (down to room temperature within 3-5 seconds) is performed on the area intended to be the bending zone, and slow cooling (10°C / min) is performed on the remaining areas to room temperature.

[0041] In the above process, the selection of key process parameters is mainly based on the following considerations:

[0042] PLA melting temperature and viscosity: Too low melting temperature (<200°C) will lead to excessive viscosity and insufficient penetration, too high temperature (>220°C) will easily cause PLA degradation, and too low viscosity is not conducive to the formation of a continuous phase in the PET pores. Controlling the viscosity in the range of 2000-3000mPa·s is conducive to penetration and ensures the stability of the PLA melt.

[0043] Vacuum degree and holding time: According to previous tests, PLA can better penetrate into the pores of the inner PET non-woven fabric by holding at a vacuum degree of -0.08~-0.1MPa for 3-5 minutes. The vacuum environment can remove the air in the pores and increase the contact area and wettability between the PLA melt and the PET fiber.

[0044] Secondary heating temperature: 90-110°C is selected. On the one hand, it converts PLA into a thermoplastic state, which is conducive to regulating its crystallization behavior through differential cooling; on the other hand, it is lower than the melting point of PLA (about 175°C) to avoid destroying the formed PET / PLA composite structure.

[0045] Differentiated cooling parameters: The inner bending zone is cooled quickly (3-5 seconds to room temperature) to increase the crystallinity of PLA in this area and increase its rigidity; the non-bending zone is cooled slowly (10°C / min) to maintain low crystallinity and rigidity. The gradient of rigidity in the two zones helps to improve the overall flexibility and wrinkle resistance of the bag.

[0046] PLA also acts as a "binder" during the penetration process, significantly improving the bonding strength between non-woven fabric layers. The three materials have good compatibility, and there is no obvious interface stratification during the molding process. Differential crystallization is the key to achieving gradient mechanical properties, which not only ensures that the parts with high bending frequency have sufficient rigidity and load-bearing capacity, but also gives the non-bending area the required softness.

[0047] In order to ensure the stability of the manufacturing process and the consistency of product quality, it is necessary to strictly control the key process parameters and implement online monitoring. The following is an explanation of them from three aspects: raw material parameters, molding process and quality inspection.

[0048] The needle punching density of the inner PET nonwoven directly determines its porosity, which in turn affects the penetration effect and mechanical properties of PLA. Through systematic experiments, the quantitative relationship between needle punching density and porosity was obtained:

[0049] ;

[0050] Considering the strength and penetration performance, 1000 needles / cm was selected in this study. 2The needle density corresponds to a porosity of about 34%, which ensures sufficient PLA filling without affecting the integrity of the nonwoven fabric. It is worth noting that too high a porosity is not conducive to penetration, because larger pores will reduce the rigidity of the PET / PLA composite structure obtained by penetration.

[0051] The melt temperature and viscosity of PLA are key factors affecting the penetration effect. The melting process is controlled as follows: the temperature in the PLA melting tank is maintained at 210±5°C and the speed is 50-100rpm by a temperature controller; the viscosity is measured every 5 minutes with an online viscometer to ensure that the fluctuation is less than 5%. Stable and controllable melt temperature and viscosity are conducive to improving the repeatability of the penetration process.

[0052] The penetration process is carried out in a vacuum environment (-0.08~-0.1MPa), using a vacuum pump to evacuate, a fine-tuning valve to control the vacuum degree, and a pressure sensor for real-time monitoring. The penetration time is based on the sample thickness and the amount of PLA adsorption, and should be shortened as much as possible within the permitted range (usually 5-10 seconds), which can reduce energy consumption and avoid PLA degradation caused by staying at high temperature for too long.

[0053] The composite material is reheated in an infrared heating furnace. An infrared thermometer is installed in the furnace cavity to monitor and adjust the temperature gradient in real time to ensure that the temperature difference between the inside and outside does not exceed 5°C. Cold air spray is used for rapid cooling of the bending zone, requiring the temperature to drop from 95°C to below 30°C within 3 seconds; the non-bending zone is placed in an insulation box for slow cooling, dropping from 95°C to room temperature within 10 minutes, and the temperature gradient is controlled at about 0.5°C / s. The experiment found that the greater the temperature gradient, the more obvious the difference in mechanical properties between the bending zone and the non-bending zone.

[0054] The T-type peeling method was used to determine the bonding strength between the film layer and the surface layer, focusing on the difference between the bending area and the non-bending area. At the same time, the gas permeation method was used to determine the change in porosity before and after PLA filling, and the filling rate of PLA was calculated based on this. The experiment showed that when the PLA filling rate reached more than 30%, the overall performance of the composite structure was good. Interlayer bonding strength and filling rate are two important indicators to characterize the integrity of the internal structure.

[0055] Ultrasonic C-scan and X-ray imaging are used to perform non-destructive testing on the inside of the product to promptly detect possible defects such as delamination, cracks, and unfilled areas. The resolution of ultrasonic C-scan can reach 0.1mm, and the detection accuracy of X-ray imaging can reach 0.05mm, which can provide data support for the quantitative evaluation of defects. Online testing helps to achieve process control of product quality and timely optimize and adjust relevant process parameters.

[0056] In order to verify the effectiveness of the manufacturing technology proposed in the present invention, 6 groups of samples with different ratios and processes were prepared, of which group AE was the control group and group F was the experimental group prepared by the technology of the present invention, and the number of samples in each group was not less than 30. The following performance indicators were mainly investigated: tensile strength, elongation at break, tear strength, bending resistance, wear resistance, antibacterial property, and flame retardancy.

[0057] Table 1 shows the average performance test results of each group of samples. It can be seen that the performance of group F in strength, toughness and functionality is better than that of other groups. The tensile strength can reach 39.5MPa and the elongation at break is 56%, which are 2.1 times and 1.5 times that of group A respectively.

[0058] Table 1:

[0059] ;

[0060] Compared with ordinary PET, the addition of hydrophobic treatment and UV absorber (groups D, E, and F) improves the weather resistance and anti-aging performance of the handbag. The addition of PU film (group BF) to the three-layer structure improves the overall strength of the handbag, and the middle PET fiber mesh layer (group CF) further provides a PLA penetration channel, which helps to form a more orderly and dense PET / PLA composite structure. Group F uses a high-porosity inner layer and a differentiated PLA penetration process, and its performance in tensile strength, elongation at break, and bending resistance is particularly outstanding.

[0061] Table 2 compares the functional test results of each group of samples. Group A is a common PET bag, and the other groups are all antibacterial and flame retardant. It can be seen that the bag of group F prepared by the technology of the present invention has a high antibacterial rate (>99%) and flame retardancy (UL 94V-0 grade) while maintaining excellent mechanical properties.

[0062] Table 2:

[0063] ;

[0064] In addition, the multi-layer structure also significantly improves the air permeability and moisture permeability of the handbag. Compared with group A, the moisture permeability of group F is reduced by nearly 40%, which means that the dry environment inside the handbag is more conducive to the storage and preservation of items. Considering the mechanical properties and functionality, group F samples are undoubtedly the best choice.

[0065] On the basis of determining the proportion of group F, the influence of different process parameters on the performance of handbags was further investigated. Figure 1The relationship curve between PLA permeability and tensile strength and elongation at break is given. As the permeability increases from 10% to 40%, the tensile strength and elongation at break show a trend of first increasing and then decreasing, reaching the optimum at around 30%. This is mainly because when the permeability is too low, the PLA content is insufficient and the reinforcing effect on the PET matrix is ​​limited; when the permeability is too high, the filling is too much, which destroys the integrity of the PET fiber to a certain extent. Therefore, the key to process optimization is to control the formation of a continuous and uniform permeation layer of PLA in the PET pores.

[0066] Figure 2 The effect of the secondary heating temperature on the stiffness of the bending zone and the non-bending zone is shown. When the temperature increases from 80°C to 120°C, the stiffness of the bending zone increases significantly, while the stiffness of the non-bending zone decreases slightly, and the difference between the two gradually widens. The reason is that the higher secondary heating temperature causes PLA to crystallize to varying degrees. In the subsequent rapid and slow cooling process, the crystallinity of PLA in the bending zone is higher than that in the non-bending zone, thus showing higher rigidity. When the temperature exceeds 120°C, the crystallinity of the non-bending zone also increases, and the stiffness difference decreases. In order to obtain an ideal mechanical property gradient, the secondary heating temperature should be controlled at 90-110°C.

[0067] In addition to groups A, B, C, D, and E, the focus is on group F (using high-porosity PET, PLA infiltration and differentiated cooling process). In order to evaluate the process stability, three batches of group F were produced (F1, F2, and F3), and 10 samples were prepared in each batch and randomly numbered. Tables 3 (1)-(3) show the average performance and standard deviation of group F samples.

[0068] Table 3 (1) PLA permeability and interlayer bonding strength:

[0069] ;

[0070] It can be seen that the PLA permeability of group F is stable at 28-29%, and the interlayer bonding strength is 17.5-17.8 N / cm, which is similar to that of group D (about 17.5 N / cm in group D), indicating that the interlayer bonding is not damaged after the introduction of PLA.

[0071] Table 3 (2) Mechanical properties and bending fatigue life:

[0072] ;

[0073] The tensile, tearing and bending fatigue life of group F are all improved compared with group D. The improvement of bending life by about 10,000 times is due to the high stiffness of the bending area and the overall performance gradient design.

[0074] Table 3 (3) Bending zone stiffness and non-bending zone flexibility:

[0075] The stiffness was tested by compression in the bending and non-bending areas using a micro-indenter (characterized by compression characteristics). The results are as follows:

[0076] ;

[0077] The stiffness of the bending zone of group F is significantly higher than that of the non-bending zones of groups D and F, proving that differentiated cooling successfully introduces regional performance gradients, making the bending zone stronger and more durable, while the non-bending zone remains relatively flexible.

[0078] Table 4 shows the test data of load-bearing limit, functional performance (hydrophobicity, air permeability, antibacterial rate, wear resistance and UV aging retention rate) of different sample groups, all of which are the average value and standard deviation of three repeated tests:

[0079] Table 4:

[0080] ;

[0081] Load limit: Group F is approximately 19.0kg ±0.5kg, which is further improved compared to Group D's 17.5kg.

[0082] Functional performance (taking F group F1 as an example):

[0083] Hydrophobicity (water contact angle): 136°±3°, similar to group D (138°±2°).

[0084] WVTR air permeability: 1200-1250g / (m²·24h), equivalent to group D.

[0085] Antibacterial rate: about 99.5%, no significant difference from group D.

[0086] Wear resistance times (ring grinder test): 4100±100 times, equivalent to group D (4000±120 times).

[0087] UV aging retention rate: about 93%, slightly better than group D's 92%.

[0088] In order to verify the stability of the process, three batches of production (numbered F1, F2, and F3) were tested for the load limit and tensile strength of group F. The results are shown in Table 5-6:

[0089] Table 5 Load limit (batch data):

[0090] ;

[0091] Table 6 Tensile strength (batch data):

[0092] ;

[0093] The average load limits of the three batches were all close to 19.0 kg, the standard deviations were in the range of 0.3 to 0.5, and the coefficients of variation (CV) were all less than 3%, indicating that the results between batches were highly consistent and the production process was stable.

[0094] The average tensile strengths of the three batches were 39.5, 39.2, and 39.7 MPa, respectively, and the coefficient of variation (CV) was approximately 3.0%, indicating good process repeatability.

[0095] The above data verify that the process parameters of high-porosity PET needle-punched nonwoven fabric and PLA infiltration and differentiated cooling technology are reasonable and stable, suitable for mass production.

[0096] After optimization, the manufacturing technology of the present invention can make the main performance indicators of the handbag reach the following levels: tensile strength ≥35MPa, elongation at break ≥50%, tear strength ≥55N, bending resistance ≥3.0x 10 4 The antibacterial rate is >99%, the flame retardancy meets UL 94V-0 level, and the moisture permeability is <1800g / (m²•24h). Compared with conventional processes, the present invention not only has obvious advantages in product performance, but also can reduce energy consumption by more than 20%, increase production efficiency by 30%, and reduce comprehensive costs by 15-20%, with significant economic and environmental benefits.

[0097] This paper proposes a new type of multi-layer non-woven handbag manufacturing technology and its key process parameters. The main conclusions are as follows:

[0098] (1) The designed "PET hydrophobic outer layer / PU&PET functional middle layer / high-porous PET load-bearing inner layer" sandwich structure has significantly improved mechanical properties, service life and functionality compared to the traditional single-layer structure, and is particularly suitable for manufacturing high-end, multi-functional handbag products.

[0099] (2) An innovative vacuum-assisted PLA infiltration process is used to uniformly fill PLA into the pores of PET fibers. A gradient crystallized PLA / PET composite structure is obtained through secondary heating and local rapid cooling, which effectively solves the contradiction between flexibility and rigidity, and air permeability and strength of conventional handbags.

[0100] (3) Through online detection methods, precise control of raw material properties (porosity, PLA viscosity), molding process (vacuum degree, temperature field, penetration time) and product quality (bonding strength, defects) is achieved, ensuring process stability and batch-to-batch consistency.

[0101] (4) Experimental results show that the manufacturing technology proposed in the present invention can produce high-performance handbag products with tensile strength ≥35MPa, elongation at break ≥50%, antibacterial rate >99%, and flame retardancy up to UL 94V-0 level, which has significant comprehensive benefits compared with conventional processes.

Claims

1. A process for manufacturing a leakproof load-bearing non-woven fabric handbag, characterized in that: The process comprises the following steps: Step 1. Process and assemble three layers of functional materials, including an outer protective layer, a middle functional layer and an inner load-bearing layer; Step 2: Using vacuum-assisted technology to infiltrate the molten PLA material into the multilayer structure to form a composite system; Step 3: Use temperature control technology to achieve differentiated distribution of mechanical properties in different areas of the product, specifically: The composite material that has completed the primary curing is placed in a heating furnace equipped with an infrared thermometer, and the temperature is raised to 90-110°C and maintained for 3-5 minutes. During this process, the temperature gradient is monitored and adjusted to ensure that the temperature difference between the inside and outside of the material does not exceed 5°C. Then, a differential cooling treatment is performed. For the predetermined bending area, the temperature is reduced from 95°C to below 30°C within 3 seconds by using a cold air spray method; for the non-bending area, it is placed in an incubator and the temperature is slowly reduced from 95°C to room temperature within 10 minutes at a constant cooling rate of 10°C / min; Step 4: Use the T-peel method to determine the interlayer bonding strength, detect the filling rate of PLA, and determine the change in porosity through the gas permeation method. Then perform functional performance testing, including testing the antibacterial rate, using standard methods to test flame retardancy, and testing moisture permeability. Finally, perform structural defect detection, using ultrasonic C-scan with a resolution of 0.1 mm and X-ray imaging technology with an accuracy of 0.05 mm to perform non-destructive testing on the inside of the product.

2. A process for manufacturing a leakproof load-bearing non-woven fabric handbag according to claim 1, characterized in that: The step 1 specifically includes: First, the outer layer of PET or PP non-woven fabric is functionally treated by adding a hydrophobic agent with a concentration of 0.5-1.0% and a UV absorber with a concentration of 0.2-0.3%. The treated material is then dried at 120°C for 10-15 minutes. Then, the middle functional layer is prepared by compounding the fiber with antibacterial, flame retardant and odor adsorption functions with a PTFE or PU microporous membrane with a thickness of 20-30μm. The membrane layer is firmly fixed on the fiber net with a density of 15-30g / m² by light pressing or low-temperature point bonding to form an intermediate layer structure with multiple functions. Finally, the inner layer of high-porosity PET needle-punched non-woven fabric is prepared, and the porosity of it is 30-40% by precisely controlling the needle density in the range of 800-1200 needles / cm².

3. The process for manufacturing a leakproof load-bearing non-woven fabric handbag according to claim 1, characterized in that: The step 2 specifically includes: First, PLA is melt-treated, PLA particles are heated to 200-220°C, melt viscosity is strictly controlled to be maintained within the range of 2000-3000mPa·s, stirring speed is maintained at 50-100rpm, and an online viscometer is used to detect once every 5 minutes to ensure that the viscosity fluctuation does not exceed 5%. Then, the prepared outer layer, middle layer and inner layer are stacked in sequence and placed in a vacuum chamber. The vacuum degree is pumped to -0.08~-0.1MPa by a vacuum pump, and maintained for 3-5 minutes under the vacuum environment and temperature conditions, so that the PLA melt can fully penetrate into the pores of the inner layer PET non-woven fabric. After the penetration is completed, cold air at 5-10°C is immediately introduced for rapid cooling for 5-10 seconds to achieve preliminary solidification of PLA in the pores of the PET fibers.

4. A leakproof load-bearing non-woven fabric handbag, characterized in that: The manufacturing process of the handbag is as claimed in any one of claims 1-3.

Citation Information

Patent Citations

  • Water and oil resistant paper-based composite bag and production method thereof

    CN106087584A

  • Film-coated heat preservation bag and manufacturing method thereof

    CN118812953A